2020
DOI: 10.1002/mrm.28185
|View full text |Cite
|
Sign up to set email alerts
|

The 2016 QSM Challenge: Lessons learned and considerations for a future challenge design

Abstract: Purpose: The 4th International Workshop on MRI Phase Contrast and QSM (2016, Graz, Austria) hosted the first QSM Challenge. A single-orientation gradient recalled echo acquisition was provided, along with COSMOS and the χ 33 STI component as ground truths. The submitted solutions differed more than expected depending on the error metric used for optimization and were generally over-regularized. This raised (unanswered) questions about the ground truths and the metrics utilized. Methods: We investigated the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 46 publications
0
28
0
Order By: Relevance
“…Reconstruction quality metrics with respect to COSMOS are provided for reference in the Supporting Information Table S1. As reported in Milovic et al, 35 these metrics should not be considered as proper error metrics because both COSMOS and χ 33 (Susceptibility Tensor Imaging, STI) ground truths incorporate anisotropic and microstructural contributions that are not present in the single-orientation acquisition, creating significant discrepancies. [35][36][37] This results in overregularized reconstructions when using such metrics and ground-truth data sets for parameter optimization.…”
Section: In Vivo Datamentioning
confidence: 99%
“…Reconstruction quality metrics with respect to COSMOS are provided for reference in the Supporting Information Table S1. As reported in Milovic et al, 35 these metrics should not be considered as proper error metrics because both COSMOS and χ 33 (Susceptibility Tensor Imaging, STI) ground truths incorporate anisotropic and microstructural contributions that are not present in the single-orientation acquisition, creating significant discrepancies. [35][36][37] This results in overregularized reconstructions when using such metrics and ground-truth data sets for parameter optimization.…”
Section: In Vivo Datamentioning
confidence: 99%
“…If the input phase data contains only information compatible with the magnetic dipole convolutional model, it is to be expected that most of the global metrics tend to produce the same optimal reconstruction parameters for a given algorithm 16 . Phase data inconsistencies or external contributions lead to a disagreement of the optimal parameters 16 , as shown in RC1. Given that RC2 consists of phantom-based forward simulations, to avoid unnecessary complexity in the challenge design (winning categories), only RMSE-based metrics were chosen to officialy evaluate the global performance of the submissions.…”
Section: Methods (Challenge Design)mentioning
confidence: 99%
“…Despite its success as a benchmark dataset, the challenge itself had limitations that limited its practical relevance. The limitations were discussed in the report paper, and analyzed more quantitatively in a separate manuscript 16 . In brief, it was concluded that the estimated susceptibility tensor component χ 33 that was used as the ground-truth removed anisotropic contributions found in single-orientation phase data, which resulted in an inconsistency between the provided field map and the groundtruth susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, only one field-map obtained from those twelve orientation acquisitions was provided to challenge participants. After completion of the challenge, it was observed (13) that a non-negligible discrepancy existed between the provided frequency map and the frequency map obtained when forward-simulating the field perturbations using the provided reference susceptibility maps. Part of the discrepancies could be explained by the presence of unaccounted microstructure effects on in vivo brain phase images (14).…”
Section: Introductionmentioning
confidence: 99%
“…The rationale of this approach was that RC1 would yield the most objective and meaningful results if algorithms were evaluated using real-world in vivo data. However, at the completion of RC1, it was observed (21) that a non-negligible discrepancy existed between the provided frequency map and the frequency map obtained when the field perturbation was forward-simulated based on the provided reference susceptibility maps. It was speculated that a part of the discrepancies were related to unaccounted microstructure effects on in vivo brain phase images (22).…”
Section: Introductionmentioning
confidence: 99%